Pengembangan Digital Flipbook berbasis Dolanan Lokal untuk Meningkatkan Literasi Membaca Siswa SD di Desa Palaan pada Era Covid-19 - Tety Nur Cholifah; Adzimatnur Muslihasari (Jurnal Bidang Pendidikan Dasar, 2022)
The purpose of this study was to produce a digital flipbook based on local games to improve the reading literacy and reading literacy. The method used is the research method (R&D), researching potential and problems, gathering information, product design, design validation, design revision, initial trial, product revision, usage trial, and product revision. Data analysis used descriptive percentage and N-gain test. The results of the study were based on the average value of the validity test on digital flipbooks based on local games in the media field 94%, material field 93%, reading literacy instrument field 93%, and student response field 95%, with criteria for all fields "very feasible" used. There is an increase in the reading literacy of elementary school students and the average pretest score is 66.63 to an average posttest score of 86.63 with an N-gain value of 0.71 which is included in the high category score.